Prevalence of Listeria monoctogenes in foods in Malaysia - Arumugaswamy, Rama K.; Rahamat Ali, Gulam Rusul; Abd. Hamid, Siti Nadzriah (Elsevier Science B.V., 1994)
A total of 234 samples of food, consisting of 158 of raw and 76 samples of ready-to-eat food were examined for the presence of Listeria monocytogenes. The frequencies of L. monocytogenes contamination in raw foods were: chicken portions (60%), liver (60%) and gizzard (62%), beef (50%), beansprout (85%), prawns (44%), kupang (dried oysters) (33%), bean cake (25%), satay (48%) and leafy vegetables (22%). Of the ready-to-eat foods: satay (26%), prawns, squids, clams and chicken dishes (22%), cucumber (80%) and peanut sauce (20%) were found to yield L. monocytogenes.